“De Olho no Óleo”, educational video. Innovation technology for teaching: experience report (Research, Society and Development, 2021)
This article aimed to characterize the process of creating the educational video De Olho no Óleo and how this video can serve as an example for new teaching strategies with an easy and functional profile. It is an experience report. By developing teaching strategies that enable the construction of knowledge, it has been a constant alternative in science education. This work showed a relatively simple initiative to create a video as an option for disseminating educational information. The development goal was to generate educational material to elucidate the correct ways to dispose and process domestic oil. The process showed that simple teaching tools can become innovative in practice.